Population structure and canopy use by Coussapoa microcarpa, a strangler hemiepiphyte from the Brazilian Atlantic Forest - Coelho, Luís Francisco Mello [UNESP]; Pizo, Marco Aurélio [UNESP] (Cambridge University Press (CUP), 2013)
We studied density, size structure, and establishment sites of Coussapoa microcarpa in the Brazilian Atlantic rain forest. This species is a hemiepiphyte that begins its life in the tops of trees and survives the death of its host to become a free-standing tree. All individuals of C. microcarpa already rooted in the ground were recorded in a 3.43 ha (1.75 ha in lowland and 1.68 ha in submontane) sample of forest plots. Data on total height, root diameter at breast height, host height and diameter at breast height, as well as height, type and diameter of the establishment site were collected. Coussapoa microcarpa present a high density (36.5 ind. ha-1) and the population studied was composed mainly of young individuals. Young and adults differed in establishment sites. The diameter of establishment sites of young was narrower than the diameter of establishment sites of adults, which points out to a limiting factor (diameter of establishment site) regulating the establishment of C. microcarpa. © 2013 Cambridge University Press.
Keywords: canopy ecology; Cecropiaceae; establishment site; primary hemiepiphyte; tropical forest; epiphyte; forest canopy; population density; population structure; rainforest; size structure; Atlantic Forest; Brazil